EFFECT OF ADDITIVE ZEOLITE MATERIALS ON THE STRENGTH OF RED BRICK POST BURNING - Prima Eko Agustyawan; Samsul Arif (U Karst, 2020)
This research aims to determine how to make bricks with additive Zeolite with a composition of 14%, 16%, 18%, and 20%. This research method using the experimental method, this research concludes that red bricks are added with additive Zeolite with variations in the addition of 14%, 16%, 18%, and 20%. 2 samples were made for each additional percentage of Zeolite Additive, with the mold size according to the fabrication length 21 cm x 10 cm x 5 cm. By going through the drying process for approximately 14 days and burning for approximately 3 days. The resulting increase in compressive strength even though some of the variants experienced a decrease. The addition of the red brick variant with a composition of 0% produces an average compressive strength of 30.95 kg / cm2Â . The 14% variant produces an average compressive strength of 35.71 kg / cm2, the 16% variant produces an average compressive strength of 40.48 kg / cm2, 18% and 20% variants produces an average compressive strength of 33.33 kg / cm2. The highest increase in compressive strength is the 16% variant, with an average compressive strength value of 40.48 kg / cm2